The Training Setting as a Social and Liminal Space for Professional Hybridization - Scaratti, Giuseppe; Fregnan, Ezio; Ivaldi, Silvia (Frontiers in Psychology, 2021)
This article addresses the liminality concept as a way to explore a particular group context, relating to a training setting intended as a liminal space, and to highlight its potential to trigger evolutionary personal and organizational identity trajectories. Dealing with a contemporary uncertain, volatile, and ambiguous organizational scenario, people are asked for consistent and quick professional hybridization processes. This article refers to a case study related to an action research process aimed at a cultural transformation and nurturing organizational learning inside an extra-hospital Rehabilitation Center, challenged by a strong organizational reconfiguration and the creation of new functions and roles, among which the one coordinator, responsible for the operational activity to be managed within the units of the organizational context. This article also highlights both the main features that characterize a training setting as a liminal space and identifies the possible plots of professional hybridization paths that a training group as a liminal space can trigger and develop.